Groundwater salinization and associated co-contamination risk increase severe drinking water vulnerabilities in the southwestern coast of Bangladesh. (May 2020) - Rakib, M.A.; Sasaki, Jun; Matsuda, Hirotaka; Quraishi, Shamshad B.; Mahmud, Md. Juel; Bodrud-Doza, Md.; Ullah, A.K.M. Atique; Fatema, Konica J.; Newaz, Md. Asif; Bhuiyan, Mohammad A.H.
Abstract: Household drinking water security is one of the major issues among coastal communities in Bangladesh. To examine the groundwater quality and social consequences, groundwater samples and household questionnaires were administered across the study area. Instrumental and statistical tools were used to analyze the water quality and social survey data. The average concentrations of electrical conductivity (EC) (7135.67 μS/cm), total dissolved solids (TDS) (3691 mg/L), Na + (1569.51 mg/L), Ca 2+ (289.5 mg/L), Mg 2+ (340.51 mg/L), Cl − (2940.78 mg/L), F − (11.85 mg/L), NO3 − (54.44 mg/L), NO2 − (162.95 mg/L), PO4 3− (105.19 mg/L), Fe (4.9 mg/L), Mn (1.22 mg/L), As (16.55 μg/L), B (833.28 μg/L), and Pb (34.22 μg/L) were observed in groundwater, and exceeded the drinking water standards from 30% to 100% depending on the sampling location. Thus, the remarkably high contents of EC, TDS, Cl −, and Na + represented possible saltwater intrusion along the coastal aquifer. The positive correlations between EC and trace and toxic elements indicated the potential influence of groundwater salinization on the dissolution of more chemical contaminants in the aquifer. These results showed that 100% of samples were unsuitable for drinking purposes. Severe drinking water scarcity is a serious issue, and local people have been affected by water-related diseases owing to the long-term consumption of contaminated water. Salinity problems in drinking water and related health diseases have increased significantly in the past several years. In addition, climate change and its associated hazards, including sea-level rise, cyclonic storm surges, flooding, and resulting inundation problems, have intensified the drinking water scarcity and health problems at the community level. To ensure household water security, environmental exposure, hydrogeology, and anthropogenic interventions must be considered to determine future sustainable water policies. Highlights: Groundwater was severely contaminated owing to salinity intrusion. High concentrations of EC, TDS, and Cl − and low pH increased the co-contamination risk, such as from trace metals. High concentrations of co-contaminants in groundwater are a great concern for future drinking water security among coastal communities. Groundwater was completely unsuitable for drinking, which poses a significant public health risk. Statistical analysis showed a significant correlation between salinity and trace elements contamination, which was found to be consistent with local perceptions.